2013
DOI: 10.5897/jmpr12.659
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of Satureja hortensis alcoholic extract against Aspergillus and Candida species

Abstract: Pharmacological and biological investigations have justified the traditional application of Satureja hortensis as a natural source of compounds for food conservation, as well as in the treatment of ailments including inflammatory diseases, cramps, muscle pains, nausea, indigestion, diarrhea, and infectious diseases. Regarding to the low number of reports of Satureja hortensis antifungal activities, we focused on the inhibitory and fungicidal effects of the Satureja alcoholic extract on Candida and Aspergillus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…It is well known that the composition, quality and content of EOs are subject to a great variation and are influenced by diverse factors such as the geographical and climatic conditions, as well as the conditions used for culture, drying and storage, the harvesting season, or differences in oil extraction techniques. Consequently, these variations can have a repercussion on the biological activity of EOs [7,10,11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the composition, quality and content of EOs are subject to a great variation and are influenced by diverse factors such as the geographical and climatic conditions, as well as the conditions used for culture, drying and storage, the harvesting season, or differences in oil extraction techniques. Consequently, these variations can have a repercussion on the biological activity of EOs [7,10,11].…”
Section: Resultsmentioning
confidence: 99%
“…Many of the natural products containing EOs and their constituents have antimicrobial properties, while several studies have shown high sensitivity of pathogenic fungi, including yeasts, to EOs [2,[5][6][7][8]. According to Waller et al [9][10][11], 55 botanical species belonging to 27 genus exhibit antifungal effects, especially the aromatic plants, notably Origanum vulgare L., Satureja hortensis L., Thymus serpyllum L. and Thymus vulgaris L. from the Lamiaceae family. These plants are a rich source of EOs [6,12,13], the major components of which may belong to several classes of compounds, mainly terpenes, such as thymol and carvacrol [12,14].…”
Section: Introductionmentioning
confidence: 99%
“…Carvacrol and thymol, and the effective constituents of S. hortensis L., may be useful in controlling aflatoxin contamination of susceptible crops in the field [ 47 ]. Kambiz et al [ 48 ] clearly demonstrate that the alcoholic extract of S. hortensis contains compounds possessing antifungal properties. The alcoholic extract of S. hortensis showed antifungal activity against phytopathogenic fungi [ 49 ] and against food spoilage fungi [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, propolis extracts in the study were highly effective to the fungal species than the bacterial counterparts (Petruzzi et al 2020 ). Kambiz et al ( 2013 ) reported that propolis extracts at a concentration of 0.125 g/L demonstrated effective anti-fungal activity against Aspergillus niger , which resulted in morphological changes on the cell membrane (Fig. 2D, E ).…”
Section: Anti-microbial Activities Of Propolismentioning
confidence: 94%